The Kitab Kuning Learning Model in the Development of Student Expertise in Pesantren-Based Higher Education - Muhamad Arif; Ridlwan Nasir; Muhammad Anas Ma’arif (Nazhruna: Jurnal Pendidikan Islam, 2025)
Kitab Kuning (Turats) is an Islamic intellectual tradition that must be preserved as an added value in Pesantren (Islamic Boarding Schools). Additionally, universities based on Islamic boarding schools have created an intriguing environment that must maintain the tradition of turats learning in academic settings while adhering to the general education trend. This research aimed to investigate 1) the implementation of turats learning at Kiai Abdullah Faqih University Gresik and 2) how the turats learning model contributes to developing student expertise at Kiai Abdullah Faqih University Gresik. The research employed a qualitative case study approach, employing data collection techniques such as documentation, archival recordings, interviews, and observations. These observations were analyzed using Yin theory, pattern matching, explanation, time series analysis, and repeated observations. The research results indicate that learning involves three stages: planning, implementation, and evaluation. In the interim, the turats learning model at Kiai Abdullah Faqih University Gresik is a contextual literacy learning (CLL) model that employs five learning syntaxes: determining material, text study, question and answer, task (contextual), and closing. This model is accompanied by learning approaches, methods, and techniques. Although this research has been restricted to a single research locus, it has yielded findings regarding the theoretical implications of the turats learning model in the development of student expertise at Islamic boarding school-based universities (Kiai Abdullah Faqih Gresik University) through the use of the contextual literacy learning (CLL) model.